Synthesis and electrochemical performance of Fe2(MoO4)3 cathode for sodium-ion batteries - Tu, Nguyen Van; Huy, Phan Quang (Vietnam Journal of Chemistry, 2016)
In this articles, Fe2(MoO4)3 was prepared by precipitation method and used as cathode materials for sodium-ion batteries. The crystalline structure of the sample was characterized by a powder X-ray diffraction spectroscopy (XRD), the morphologies of the sample were observed by the field emission scanning electron microscopy (SEM), the binding state of elements in sample was analyzed by X-ray photoelectron spectroscopy (XPS). The electrochemical properties were investigated in CR2025 coin type cell with a metal sodium foil as the anode electrode. As the charge/discharge current density at 0.1 C, the initial specific capacity of Fe2(MoO4)3 is 82.50 mAhg-1, and remains 67.92 mAhg-1 after 15 cycles. Keywords. NASICON, iron molybdate, sodium ion battery, cathode material.